Impact of Government Expenditure on Economic Growth: Evidence from Nigeria - Bappahyaya, Bashir; Abiah, Fada K.; Bello, Farida (European Scientific Journal, ESJ, 2020)
This study seeks to explain the impact of government expenditure on economic growth in Nigeria using time series data from 1970 – 2017. Secondary data were sourced from Central Bank of Nigeria and World Bank. The study applied a modified version of endogenous growth model using Autoregressive distributed lag model. The adopted model was fitted with six variables- capital stock, labour force, capital expenditure, recurrent expenditure, inflation and trade openness. The study employed ADF-unit root test, Phillips-Perron test and Pairwise Granger causality test. All the variables used were found to be integrated at first difference except labour and inflation and a stable long run equilibrium relationship exist between the dependent and independent variables. Empirical findings revealed that two variables: capital and recurrent are statistically significant and hence these are the significant variables in explaining the impact of government expenditure on economic growth. The Granger causality test demonstrates a unidirectional causality from government expenditure to economic growth, in validation of Keynesian theory. In line with above, the study recommends among others that: government should intensify effort to ensure resources are properly managed and invested in productive sectors so as to foster economic growth.